TEACHERS’ STRATEGIES TO DEVELOPING STUDENTS’ SPIRITUAL INTELLIGENCE AT VOCATIONAL SCHOOL - Agustina, Henri; Harfiani, Rizka; Setiawan, Hasrian Rudi (JURNAL TARBIYAH, 2024)
This research aims to analyze teachers' strategies in developing the spiritual intelligence of Galang Insan Mandiri Binjai Health Vocational School students. To reveal the findings, a qualitative approach was used with analytical descriptive methods. Data collection steps start from observation, interviews and documentation, then the data is analyzed through stages and techniques in the form of data reduction, data presentation and conclusions. Finally, the data was declared valid after going through a research data triangulation test. The results of the research found that fostering students' spiritual intelligence at school experienced obstacles, namely due to environmental factors, low self-awareness, different family education patterns, and a lack of response from students' parents. The strategies implemented by teachers to overcome these obstacles, namely holding student guardian meetings, carrying out recitation activities with students and student guardians, as well as religious activities at school.